Promoting biogas and biomethane production: Lessons from cross country studies - Tong Zhu; John A. Curtis; Matthew S. Clancy (The Economic and Social Research Institute (ESRI), 2019)
While a rich body of literature has looked at greenhouse gas emissions in biogas production systems and the potential impacts of biogas production on food supply, broader issues relating to the economic, environmental and social pillars of sustainability need to be carefully considered. Drawing upon experiences from European countries, we identify key outcomes associated with large-scale implementation of biogas and biomethane production. Topics of particular interest include policy instruments, farm intensification, and supply chain risks. We conclude by recommending policy directions for countries such as Ireland that are at earlier developmental stages for biogas and biomethane deployment.
Keywords: 330; renewable energy; biogas; biomethane; anaerobic digestion; greenhouse gas emissions; agricultural sector